Scavenging of sulphur, halogens and trace metals by volcanic ash: The 2010 Eyjafjallajökull eruption - Bagnato, E.; Aiuppa, A.; Bertagnini, A.; Bonadonna, Costanza; Cioni, R.; Pistolesi, M.; Pedone, M.; Hoskuldsson, A. (Geochimica et Cosmochimica Acta, 2013)
The Eyjafjallajökull volcanic eruption in 2010 released considerable amounts of ash into the high troposphere-low stratosphere, leading to unprecedented disruption of air traffic over Europe. The role of such fine-grained tephra in adsorbing, and therefore rapidly scavenging, volcanogenic volatile elements such as sulphur and halogens, is explored here. We report on results (major to trace element chemistry) of leaching experiments carried out on 20 volcanic ash samples, taken from the deposits of the main phases of the eruption (March–April 2010), or directly while falling (5–9 May 2010). Ash leachate solutions from Eyjafjallajökull are dominated – among cations – by Ca and Na, and display nearly equal S:Cl:F abundances (mean S/Cl and S/F molar ratios of 0.95 and 0.34, respectively). Abundances of major elements on surface minerals from freshly fallen ash are found to increase linearly upon increasing distance from the eruptive vents (a proxy for in-plume residence times). This allows for the formation rates of sulphur- and halogen-bearing surface salts to be quantified (3 × 10−9 to 2 × 10−8 mol m2 s−1), and for the averaged rate of in-plume ash-dissolution to be estimated (1.5 × 10−8 mol m−2 s−1; this sourcing the majority of cation species to soluble surface salts). These fast in-plume heterogeneous reactions are the cause of large volatile depositions: we estimate that 282 tons of elemental S, 605 tons of Cl, and 691 tons of F were daily ground deposited via ash over Iceland in early May 2010. Since fluorine is ∼3 times more rapidly processed in the plume than S and halogens (e.g., F is extremely reactive both in gas and aerosol forms and it is rapidly adsorbed onto ash), ash leachate compositions are in no way representative of S:Cl:F proportions in volcanic gases, and consequently of limited use in eruption monitoring.